2019
DOI: 10.3390/sports7050099
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Elite Short-Course Triathlon Re-Emphasises the Necessity to Transition Efficiently from Cycling to Running

Abstract: Transitioning efficiently between cycling and running is considered an indication of overall performance, and as a result the cycle–run (C–R) transition is one of the most researched areas of triathlon. Previous studies have thoroughly investigated the impact of prior cycling on running performance. However, with the increasing number of short-course events and the inclusion of the mixed relay at the 2020 Tokyo Olympics, efficiently transitioning from cycle–run has been re-emphasised and with it, any potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 86 publications
(203 reference statements)
0
37
0
Order By: Relevance
“…Millet and Vleck [ 7 ] stated that the first transition (i.e., swim–cycle transition) is regarded as having a negligible effect on overall performance during the nondraft legal OD race. Meanwhile, a number of studies reported the effects of prior exercise on subsequent running [ 7 , 8 , 59 , 60 , 61 ] and the cycle–run transition is traditionally considered to be more important on performance during an OD race [ 7 , 8 ]. Prior cycling induces physiological/cardiorespiratory and biomechanical changes during subsequent running [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Millet and Vleck [ 7 ] stated that the first transition (i.e., swim–cycle transition) is regarded as having a negligible effect on overall performance during the nondraft legal OD race. Meanwhile, a number of studies reported the effects of prior exercise on subsequent running [ 7 , 8 , 59 , 60 , 61 ] and the cycle–run transition is traditionally considered to be more important on performance during an OD race [ 7 , 8 ]. Prior cycling induces physiological/cardiorespiratory and biomechanical changes during subsequent running [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a number of studies reported the effects of prior exercise on subsequent running [ 7 , 8 , 59 , 60 , 61 ] and the cycle–run transition is traditionally considered to be more important on performance during an OD race [ 7 , 8 ]. Prior cycling induces physiological/cardiorespiratory and biomechanical changes during subsequent running [ 8 ]. Several studies have reported that such changes (usually negative effects) might be related to the performance level of triathletes [ 62 , 63 , 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a triathlon, the smooth transitioning from cycling to running is considered to be crucial for optimal performance in the final running part and the overall result [ 1 , 2 , 3 ]. The ability to quickly find one’s personal running pattern is of great importance, which contributes to optimal processes in muscular control and energy supply [ 1 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For all triathlon distances, athletes have to cope with what they colloquially describe as “brick running” (it feels like “hitting a wall of bricks”) or “running on eggs” at the beginning of the running section. This sense of incoordination, which is not found in isolated running, may result in altered running kinematics triggered by prior cycling [ 2 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%